(untitled) (Revista de Crítica Literaria Latinoamericana, 2013)
This paper explores the relationship between Octavio Paz and Surrealism. It focuses not only on the vital relationship of the poet with the French Literary Group but also on his particular aproach to the aesthethics and ethics of Surrealism. For Paz, Surrealism implied a moral philosophy and that is why he used objective chance as a tool for knowledge, logic and poetic abstraction.